Concentrações dos óxidos nitrogenados NOx (NO+NO2) na região metropolitana de Maceió-AL, em função de parâmetros meteorológicos - Fernandes, Ronabson Cardoso (2010)
The objective of this study was analyze the concentrations of nitrogen oxides in the center of the metropolitan area in Maceió, Alagoas. The data were collected from chemical parameters using a NOx analyzer (NO + NO2) API Model 200 A using the chemiluminescence method, and to monitore the atmospheric conditions (physical parameters) was used a WeatherLink Pro2 weather station from Davis Instruments (USA), where its sensors were 2 meters in height above the ground. Monitoring for the parameters had an average interval of 10 minutes. Nitrogen oxides concentrations are shown sensitive to weather changes. The highest frequencies of NO concentrations were 43,8% ranging from 10-15 ppbv and NO2 concentrations were 46,6% between 0 and 2 ppbv. It was evident that the highest concentrations were obtained during the week. The NO2 and NO concentrations for 15/07 (Thursday) during the day were nearly 309% and 153.5% higher than 12/07 (Sunday), respectively. The motor vehicles were the main source of emissions due to high atmospheric pressure increased concentrations, and with low pressures the concentrations were decreased. During the night, the weather provided some chemical reactions that were sink of NOx, so having in this period low daily concentrations. During the day, the intensity of solar radiation and the presence of cloud cover contributed to significant attenuation of concentrations of these oxides, allowing the photolysis of NO2 to form secondary pollutants harmful to health.